Cutting-Edge Solutions for Advancing Sustainable Development: Exploring Technological Horizons for Sustainability - Part 2 - Whig, Pawan; Sharma, Pavika; Yathiraju, Nikihita (Bentham Science Publishers, 2025)
Cutting-Edge Solutions for Advancing Sustainable Development: Exploring Technological Horizons for Sustainability - Part 2 introduces innovative approaches to achieving sustainability through technological advancements. This comprehensive guide covers critical global challenges such as climate change and resource depletion, emphasizing the transformative role of emerging technologies. Key Features: - Detailed exploration of blockchain applications in supply chains and financial services. - Innovations in HealthTech improving healthcare accessibility and quality. - Utilization of AI for climate action and precision agriculture. - Advancements in renewable energy technologies, focusing on solar and wind. - Societal impacts of AI automation and financial literacy in technologically enhanced learning environments.